2022
DOI: 10.5114/ada.2020.100821
|View full text |Cite
|
Sign up to set email alerts
|

Carmine allergy in urticaria patients

Abstract: Introduction Carmine, a commonly used natural red dye, can cause immediate and delayed allergic reactions, which are frequently overlooked. Aim To assess the incidence of carmine allergy and its clinical significance based on the placebo-controlled oral challenge in urticaria patients and suspected hypersensitivity to food additives. Material and methods Patients’ histories were recorded by means of a standardized questionnaire. The subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Cochineal-red-related anaphylaxis[ 5 ], urticaria[ 6 ], occupational asthma[ 7 ], and allergic contact dermatitis[ 8 ] have been reported, and the main mechanism is IgE-mediated anaphylaxis[ 9 ]. Cochineal red may be a potentially overlooked allergen in patients with chronic allergic diseases and in children[ 10 , 11 ]. Cochineal red is also a cause of occupational respiratory allergies[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cochineal-red-related anaphylaxis[ 5 ], urticaria[ 6 ], occupational asthma[ 7 ], and allergic contact dermatitis[ 8 ] have been reported, and the main mechanism is IgE-mediated anaphylaxis[ 9 ]. Cochineal red may be a potentially overlooked allergen in patients with chronic allergic diseases and in children[ 10 , 11 ]. Cochineal red is also a cause of occupational respiratory allergies[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outro aditivo da classe dos corantes, presente nos produtos analisados na categoria dos iogurtes, foi o corante carmim de cochonilha. O carmim é um corante vermelho natural comumente utilizado nas indústrias cosmética, alimentar e farmacêutica 42 . Os efeitos adversos mais destacados são os sintomas de hipersensibilidade, no qual apresenta diversas reações, dentre elas, eritema, urticária, angioedema, exacerbação do eczema atópico, broncoespasmo, bronquiolite, sintomas gastrointestinais e choque anafiláticos 42 .…”
Section: Discussionunclassified
“…Em um estudo realizado com pessoas diagnosticadas com urticária e suspeita de hipersensibilidade a aditivos alimentares, os resultados apresentados mostraram que o carmim é um alergênico potencial em doentes com urticária crônica induzível, especialmente com sintomas sistêmicos concomitantes 42 .…”
Section: Discussionunclassified
“…A total of 32 papers were screened by the FEEDAP Panel for their relevance in the assessment of the user safety for Carmine/carminic acid. Nineteen papers (Catli et al., 2015; De Pasquale et al., 2015; Gosetti et al., 2015; Liippo and Lammintausta, 2015; Miyakawa et al., 2016; Sanchez‐Machin et al., 2016; Ferris et al., 2017; Gulseren et al., 2017; Ramesh and Lieberman, 2017; Machler and Jacob, 2018; Takeo et al., 2018; Fok, 2020; Hirase et al., 2020; Lemoine et al., 2020; Morin and Sasseville, 2020; Ozceker et al., 2020; Suzuki et al., 2021; Warshaw et al., 2021; Sadowska et al., 2022) were considered by the FEEDAP Panel as relevant and confirmed that the additive should be considered as an allergen through dermal exposure. Only one single paper (Yamashita et al., 2018) reported negative effects of carmine tested for its skin sensitisation potential using a modified lymph node assay with an elicitation phase.…”
Section: Assessmentmentioning
confidence: 99%